Analisis Tingkat Indeks Massa Tubuh (IMT) dan Kondisi Fisik Pemain Futsal Putra SMAN 1 Torjun - Jailani; Handayani, Heni Yuli; Purwoto, Septyaningrum Putri (SPRINTER: Jurnal Ilmu Olahraga, 2025)
Futsal as a sport also requires proper training to achieve success. Therefore, prime physical condition is needed so that players are able to display their best performance. In addition, Body Mass Index (BMI) is also an important aspect that needs to be considered. This study aims to determine the Body Mass Index and physical condition of male Futsal players at SMAN 1 Torjun. The data collected are height, weight, age to determine the level of nutritional status, while data regarding physical condition includes data on speed of movement (speed), flexibility (flexibility), leg muscle strength, muscular endurance (muscular endurance), leg muscle explosive power (power) and endurance (aerobic). The subjects of this study were male futsal players at SMAN 1 Torjun who registered in the Amateur Futsal League. This type of research is quantitative with descriptive methods. 1) The results of data collection obtained an average height of 1.67 m, an average weight of 61.86 kg, an average BMI of 22.29 within normal criteria. The average physical condition includes 2) average speed of movement (speed) 4.20 seconds, 3) average flexibility 16.87 cm, 4) average leg muscle strength of 106.86 kg, 5) average abdominal muscle endurance (muscular endurance) 39.71 times, 6) average leg muscle explosive power (power) 264 watts and 7) average aerobic endurance of 43.06 miles/kg/min.